2020
DOI: 10.1002/fee.2255
|View full text |Cite
|
Sign up to set email alerts
|

Novel resources: opportunities for and risks to species conservation

Abstract: During the Anthropocene, ongoing rapid environmental changes are exposing many species to novel resources. However, scientists' understanding of what novel resources are and how they impact species is still rudimentary. Here, we used a resource-based approach to explore novel resources. First, we conceptualized novel resource use by species along two dimensions of novelty: namely, ecosystem novelty and resource novelty. We then examined characteristics that influence a species' response to a novel resource and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…While we have emphasized the critical role of indigenous plants, we have also shown that indigenous insects are being found in association with a wide array of regionally native and nonnative plants. Thus, our study supports the idea that urban environments facilitate novel resource utilization by indigenous insects (Padovani et al 2020, Valentine et al 2020). Future experimental work on this topic is needed to clarify to what extent these associations reflect host shifting patterns unique to urban environments and to fully understand the opportunities and risks provided by novel urban resources.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While we have emphasized the critical role of indigenous plants, we have also shown that indigenous insects are being found in association with a wide array of regionally native and nonnative plants. Thus, our study supports the idea that urban environments facilitate novel resource utilization by indigenous insects (Padovani et al 2020, Valentine et al 2020). Future experimental work on this topic is needed to clarify to what extent these associations reflect host shifting patterns unique to urban environments and to fully understand the opportunities and risks provided by novel urban resources.…”
Section: Discussionsupporting
confidence: 89%
“…Urban environments are central nodes of human‐mediated dispersal networks (Bullock et al 2018) and hotspots of novel resource utilization (Valentine et al 2020), such that introduced species are often prominent (Cadotte et al 2017, Paap et al 2017). The number of introduced insect species can be relatively low (Uno et al 2010, Madre et al 2013, Mata et al 2017), but they often occur in high abundance and this is especially the case for generalist ants, bees, and butterflies (Connor et al 2002, Matteson and Langellotto 2010, Uno et al 2010, Threlfall et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas close ecological interactions might be lost due to the introduction of exotic species (e.g. lack of seed dispersal by native species due to predation by exotic ones), others may arise when these species permeate food chains by providing new resources (Harvey et al, 2010; Pearson & Callaway, 2003; Valentine et al, 2020). Generalist and mobile species can partially cope with habitat changes and periods of native food shortage by consuming exotic resources (Kremen et al, 2007; Muñoz et al, 2007; Páez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biotic filters may have equally important, if not greater effects on invertebrate communities (see Kraft et al 2015). The high proportion of non-native plant species in urban areas results in novel resources available to urban forest invertebrates and may influence trophic and non-trophic interactions in these ecosystems (Valentine et al 2020). For instance, non-native trees as sources of organic matter for invertebrates have the potential to influence the community assembly of collembolans (Raymond- Leonard et al 2018) and mites (Malloch et al 2020), and ultimately, litter decomposition rates (Makkonen et al 2012; but see Finerty et al 2016).…”
Section: Filters Acting On Urban Forest Invertebratesmentioning
confidence: 99%